2005
DOI: 10.1016/j.palaeo.2005.03.011
|View full text |Cite
|
Sign up to set email alerts
|

A multi-proxy approach to determine Antarctic terrestrial palaeoclimate during the Late Cretaceous and Early Tertiary

Abstract: Fossil wood is abundant throughout the Cretaceous and Tertiary sequences of the northern Antarctic Peninsula region. The fossil wood represents the remains of the vegetation that once grew at the southern high palaeolatitudes at 59-628S through the general decline in climate, from the Late Cretaceous global warmth through to the mid-Eocene cool period prior to the onset of glaciation. This study draws on the largest dataset ever compiled of Antarctic conifer and angiosperm woods in order to derive clearer insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 62 publications
(97 reference statements)
4
67
1
2
Order By: Relevance
“…It is necessary, however, to consider paleoclimate data to estimate the isotope composition of meteoric water when the alteration took place. The mean annual temperature of King George Island during the Middle Eocene was generally between 12 o C and 13.3 o C (Poole et al, 2005), much higher than the present average -2.8 o C (Ferron et al, 2004). Thus, this suggests that the isotopic composition of meteoric water during the alteration process would have not been so low as that of the present time.…”
Section: Oxygen and Hydrogen Isotopesmentioning
confidence: 77%
“…It is necessary, however, to consider paleoclimate data to estimate the isotope composition of meteoric water when the alteration took place. The mean annual temperature of King George Island during the Middle Eocene was generally between 12 o C and 13.3 o C (Poole et al, 2005), much higher than the present average -2.8 o C (Ferron et al, 2004). Thus, this suggests that the isotopic composition of meteoric water during the alteration process would have not been so low as that of the present time.…”
Section: Oxygen and Hydrogen Isotopesmentioning
confidence: 77%
“…Dallai and Burgess (2011) (Ivany et al, 2011). Fossil wood from the James Ross Basin and South Shetland find diverse mid-Eocene assemblages (Poole et al, 2005), with species similar those found on Seymour Island mid-Eocene sections (Askin, 1997). The pollen records from Seymour Island (La Meseta Formation) reveal a decline in plant diversity from the mid-late Eocene (Askin, 1997) with a loss of varied Nothofagus brassii group species (Chen, 2000).…”
Section: Vegetation and Environment Of The Late Eocene On The Antarctmentioning
confidence: 88%
“…After the peak warmth of the mid-Late Cretaceous, climate appears to have cooled globally during the latest part of the Cretaceous, as seen also in the Antarctic fossil wood record (Francis and Poole, 2002;Poole et al, 2005). However, warm climates returned to the high latitudes during the Paleocene and early Eocene, as is reflected in fossil plants.…”
Section: From Greenhouse To Icehousementioning
confidence: 97%